Determining patterns in the generation of magnetic fields when using different arc welding techniques - Levchenko, Oleg; Polukarov, Yury; Goncharova, Olga; Bezushko, Olga; Arlamov, Olexandr; Zemlyanska, Olena (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports a study into the levels of magnetic fields induced by arc welding equipment in various ways in order to assess their impact on the body of welders. It is known that welders are exposed to a magnetic field of high intensity. Depending on the welding technique and the type of welding equipment, it may exceed the maximum permissible levels (MPL). Note that new Ukrainian sanitary standards for magnetic fields have been introduced, which regulate their levels depending on the frequency range. Therefore, it became necessary to carry out their hygienic assessment according to the new standards in order to devise appropriate methods for protecting welders. To this end, it was required to choose a new generation of devices to determine the intensity of magnetic fields induced by welding equipment. Based on the analysis of the constructed oscillograms and spectrograms of magnetic fields, it was found that semi-automatic welding with a metal electrode in carbon dioxide is characterized by an increased level of magnetic field in the frequency range of 50‒1000 Hz. With automatic arc welding under the flux, there are no excess of the maximum permissible levels of individual harmonics of the magnetic field but there is an excess of the total value of all harmonic components of the magnetic field. Manual arc welding with direct current involving a non-melting electrode in argon is characterized by a moderate level of magnetic field in workplace. During manual arc welding with coated electrodes, the exceeded level of the magnetic field is observed only on the electrode cable itself. It is shown that the spectral composition of the magnetic field signal is determined mainly by the welding technique itself, the peculiarities of arc combustion, and the nature of the transfer of electrode metal in the arc gap, as well as the initial parameters of the power supplies of the welding arc